Mengupas Sejarah Dam Bagong dan Eksistensi Tradisi Nyadran di Kelurahan Ngantru Kabupaten Trenggalek - Arwi Abidin; Budi Santoso; Anggoro Putranto (LPPM Politeknik Pratama, 2023)
This paper discusses the history of the bagong damand the existence of the Nyadran tradition in the Ngantru Village, Trenggalek Regency. Bagong Damhas a long history as a source of irrigation water for the surrounding agriculture. This damalso has an important role in the Nyadran tradition which is still being preserved by the local community. The Nyadran tradition is carried out as an expression of gratitude and gratitude to the ancestors who are considered as protectors and guardians of security and safety in the region. In practice, this tradition involves various cultural elements. The nyadran tradition which takes place at Bagong Dam is a part of the customs that exist in the community, namely the implementation of traditional ceremonies in which there are high cultural values and a lot of inspiration for regional cultural wealth which can add to national cultural diversity. (I) Describe the history of the Nyadran tradition of Trenggalek district; (II) Analyze the urgency of the nyadran tradition in dam bagong; (III) analysis of the values embodied in the Nyadran Dam Bagong tradition; (IV) Analysis of similar traditions in other regions. The method used is the method of literature study.